BOOSTING DIGITAL MARKETING IN ASIAN SMES THROUGH CULTURAL SENSITIVITY: SYSTEMATIC INSIGHTS AND FUTURE DIRECTIONS - Arief Bowo Prayoga Kasmo; Diah Fistiani Sukardiman; Setyo Riyanto; Unang Toto Handiman; Ubedullah Memon (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study presents a systematic literature review on the impact of culture on digital marketing, addressing a crucial gap in understanding how cultural differences shape consumer interactions with brands. Given the increasing globalization of markets and the diverse cultural backgrounds of consumers, understanding culture’s impact on marketing is critical for developing effective strategies that resonate across different regions. The study employs the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) model to systematically filter articles indexed by Scopus, utilizing the Publish or Perish tool for initial identification. Out of 1222 articles collected, 62 articles were selected after eliminating those that were not relevant to the research scope. The findings demonstrate that cultural factors significantly influence in digital marketing strategies, consumer behavior, consumer involvement, and the establishment of consumer loyalty. Theoretically, this study expands on existing marketing theories by integrating cultural dimensions into models of consumer behavior and brand engagement, emphasizing the need for culturally adaptive marketing frameworks. Practically, these findings provide marketers with insights into tailoring their strategies to accommodate cultural differences, thereby enhancing brand relevance and fostering long-term consumer loyalty. Additionally, a model framework for a future research agenda is proposed, focusing on integrating cultural variables into marketing decision-making processes. This framework aims to examine specific cultural factors and their impact on marketing at various levels, including strategy formulation, consumer engagement, and loyalty development. By understanding these relationships, marketers can develop more precise strategies that effectively connect with culturally diverse consumer groups, thereby enhancing marketing performance